Pendampingan Strategi Pengelolaan Konflik pada Organisasi Kemahasiswaan di Kota Padang - Anita Afriani Sinulingga; Maryam Jamilah; Haiyyu Darman Moenir; Syukria Ikhsan Zam (Warta Pengabdian Andalas, 2022)
The study of International Relations claims that the main agenda of learning is to create world peace, but classical IR classes talk more about narratives about war. The initiation of this community service activity departed from a critique of classical IR studies, which believed that if we want peace, we must learn about peace, not war. Conflict is something natural and unavoidable. Likewise, students managing their organizations face various conflicts. Conflicts cause students to trap in physical feuds, such as brawls and beatings of students or verbally slandering or cursing. When conflicts resolve with violence, students managing their organizations have not applied the values ​​and practices of non-violence. Understanding and managing conflict are vital for students not to become destructive. This activity targets students who are part of student organizations in the city of Padang. Activities using various methods, including material presentations, interactive discussions, and student case analysis presentations. The participants conducted an evaluation pre-test and post-test to assess the activity's effectiveness. There was a change in students' perspective and knowledge of conflict and conflicting styles at the end of the activity.